Receivables Collection for Transportation Service At PT Ciomas Ariya Samudera - Chandra Prasadhita; Muhammad Nawawi; Alinda Rakhe Yulia Putri (Journal of Applied Business, Taxation and Economics Research, 2022)
Receivables are part of the assets of an entity in the form of short-term or long-term claim rights from past economic transactions carried out by the company concerned with its clients. PT. Ciomas Ariya Samudera is a service company that focuses its business in the field of transportation services located in Cilegon Banten. The research method used in this study is a qualitative research method with a sequence of steps consisting of observations, interviews, and documentation collected from PT. Ciomas Ariya Samudera. The results obtained in the field describe the procedure for collecting receivables from transportation services at PT. Ciomas Ariya Samudera is in line with the theory.